Light-induced paramagnetism in colloidal Ag+-doped CdSe nanoplatelets - Najafi, Arman (2021)
We describe a study of the magneto-optical properties of Ag+-doped CdSe colloidal nanoplatelets (NPLs) that were grown using a novel doping technique. In this work, we used magnetic circularly polarized luminescence and magnetic circular dichroism spectroscopy to study light-induced magnetism for the first time in 2D solution-processed structures doped with nominally nonmagnetic Ag+ impurities. The excitonic circular polarization (PX) and the exciton Zeeman splitting (ΔEZ) were recorded as a function of the magnetic field (B) and temperature (T). Both ΔEZ and PX have a Brillouin-function-like dependence on B and T, verifying the presence of paramagnetism in Ag+-doped CdSe NPLs. The observed light-induced magnetism is attributed to the transformation of nonmagnetic Ag+ ions into Ag2+, which have a nonzero magnetic moment. This work points to the possibility of incorporating these nanoplatelets into spintronic devices, in which light can be used to control the spin injection.